A kind of antifreeze polymer / inorganic filler composite modified asphalt emulsion for drilling fluid and its preparation method and application
By introducing composite filler and polymer particles into the drilling fluid and using the synergistic effect of formate and alcohols, an antifreeze-type polymer/inorganic filler composite modified asphalt emulsion was prepared, which solved the problems of low-temperature storage and poor high-temperature stability of modified asphalt in the prior art, and achieved efficient sealing and temperature resistance.
Patent Information
- Application Number
- CN202310575708.9
- Authority / Receiving Office
- CN · China
- Patent Type
- Patents(China)
- Current Assignee / Owner
- Filing Date
- 2023-05-22
- Publication Date
- 2025-04-08
- Estimated Expiration
- 2043-05-22
AI Technical Summary
The existing cationic bitumen emulsion for drilling fluids has poor low temperature storage and high temperature stability, making it difficult to meet the high requirements of drilling construction for the temperature resistance and sealing performance of modified bitumen.
By introducing materials such as composite fillers and polymer particles, modified natural asphalt is prepared to obtain antifreeze polymer/inorganic filler composite modified asphalt emulsion for drilling fluids. Formate and alcohols are used to reduce the freezing point and improve colloid stability.
It significantly improves the asphalt softening point, enhances the temperature resistance and sealing performance, improves the low-temperature storage stability and high-temperature crack resistance, and meets the needs of drilling construction.
Smart Images

Figure BDA0004239870910000071 
Figure BDA0004239870910000072 
Figure BDA0004239870910000073
Abstract
Description
Technical Field
[0001] The invention relates to an antifreeze polymer / inorganic filler composite modified asphalt emulsion for drilling fluid and a preparation method and application thereof, belonging to the technical field of preparation of cationic emulsified asphalt for oil and natural gas drilling fluid treating agent. Background Art
[0002] The transportation and on-site storage temperature of cationic emulsified asphalt used in drilling fluid generally needs to be maintained between -5℃ and 25℃. Otherwise, when the storage environment temperature is lower than -5℃, it will become severely thickened or solidified, lose colloidal stability, and break the emulsion, making it unusable. Therefore, when the construction temperature of the drilling site is lower than -5℃, a special insulated vehicle is required to transport the cationic emulsified asphalt to the construction site. At the same time, the drilling site requires special insulation measures (such as insulated pipelines, etc.) for insulation storage. However, the outdoor temperature of the western and northern oil fields in my country (such as the Tarim Oilfield, etc.) in winter is close to -25℃, which brings inconvenience to the storage and use of cationic emulsified asphalt at the drilling site.
[0003] During the drilling process of ultra-deep wells in my country, it is easy to encounter collapse formations such as shale and igneous rock. The sealing and anti-collapse performance of the drilling fluid needs to be further improved on site. Adding a cationic emulsified asphalt treatment agent with a suitable softening point to the drilling fluid is a direct and efficient treatment method. The added asphalt colloid particles enter the micro-cracks and pores of the well wall to produce adhesion and mutual aggregation, filling and sealing, further improving the quality of the mud cake and reducing water loss, and improving the sealing and anti-collapse performance of the drilling fluid, thereby effectively preventing and solving the complex occurrence of collapse accidents in long open hole drilling.
[0004] Asphalt products are divided into natural asphalt, petroleum asphalt and modified asphalt. Modified asphalt products are widely used in drilling. However, the common modified asphalt products on the market have poor temperature resistance. When the modified asphalt is at the softening point temperature of the original asphalt, a phase transition occurs. However, in some strata with high temperatures and complex temperature field distribution, high performance requirements are put forward for the temperature resistance of modified asphalt, especially the low temperature storage and high temperature stability of modified asphalt. For example: Chinese patent document CN102863804A provides an SBS polymer modified emulsified asphalt and a preparation method thereof, wherein the modified emulsified asphalt is prepared from the following raw materials in mass percentage: SBS polymer modified asphalt 40-65%, water 25-50%, cationic asphalt emulsifier 2-10%, composite emulsified stabilizer 0.1-2% and acid 0.2-2%, wherein the SBS polymer modified asphalt is a mixed reaction of SBS polymer modifier and matrix asphalt, and the modified emulsified asphalt has a good ductility index at 5°C, but its low temperature resistance is still limited. Chinese patent document CN105968834A provides a high softening point emulsified asphalt, which is prepared from the following raw materials in weight percentage: 50-60% asphalt, 1-4% styrene-butadiene-styrene block copolymer, 1-6% polyolefin, 1.5-2.5% cationic asphalt emulsifier, and the balance is water. The prepared emulsified asphalt has a high softening point, but the low temperature resistance of the emulsified asphalt and the emulsion stability under low temperature conditions are poor.
[0005] Therefore, developing a modified asphalt emulsion with good temperature resistance and plugging performance and excellent low-temperature storage stability is of great significance for improving the comprehensive performance of water-based drilling fluid. Summary of the invention
[0006] In view of the shortcomings of the prior art, especially the poor low-temperature storage and high-temperature stability of the existing cationic asphalt emulsion for drilling fluid, and to improve its plugging efficiency for formation microcracks and pores to meet the needs of drilling construction, the present invention provides an antifreeze polymer / inorganic filler composite modified asphalt emulsion for drilling fluid and its preparation method and application. The present invention prepares an antifreeze polymer / inorganic filler composite modified asphalt emulsion for drilling fluid by modifying natural asphalt with materials such as composite fillers and polymer particles. The composite modified asphalt emulsion of the present invention can significantly improve the softening point of asphalt and increase its temperature resistance; the introduction of composite fillers can improve the temperature resistance of the composite modified asphalt emulsion on the one hand, and increase the plugging performance on the other hand; the introduction of polymer particles can increase the overall relative molecular mass, so that the temperature resistance of the composite modified asphalt emulsion is improved; in addition, the synergistic effect of formate and alcohol can reduce the freezing point of the composite modified asphalt emulsion and improve its colloidal stability at low temperatures.
[0007] The technical solution of the present invention is as follows:
[0008] An antifreeze polymer / inorganic filler composite modified asphalt emulsion for drilling fluid is prepared from the following raw materials in parts by mass: 80-120 parts of asphalt, 20-40 parts of composite filler, 15-30 parts of polystyrene-polyisoprene-polystyrene triblock copolymer and polypropylene composite particles, 4-12 parts of cationic emulsifier, 5-20 parts of formates, 40-60 parts of alcohols, 3-8 parts of stabilizer and 150 parts of water.
[0009] Preferably according to the present invention, the asphalt is petroleum asphalt, and the softening point of the asphalt is 80-120°C.
[0010] Preferably according to the present invention, the composite filler is a mixture of spherical calcium carbonate, flaky mica flakes and sepiolite fibers, wherein the mass ratio of the spherical calcium carbonate, flaky mica flakes and sepiolite fibers is 1-1.5:1.5-3:1; and the particle size of the composite filler is 400-800 meshes.
[0011] Preferably, according to the present invention, the polystyrene-polyisoprene-polystyrene triblock copolymer and polypropylene composite particles are prepared according to the following method: polystyrene-polyisoprene-polystyrene triblock copolymer (SIS) and polypropylene (PP) are added to a double-roller mixing mill, mixed evenly, hot-mixed to make the rubber material reach 100° C., mixed at 100° C. for 20-30 minutes to achieve mixed plasticization, then compression molded into sheet strips, and cut into 30-50 mesh particles using a pelletizer to obtain.
[0012] Further preferably, the mass ratio of the polystyrene-polyisoprene-polystyrene triblock copolymer (SIS) to polypropylene (PP) is 4.5-7:1.
[0013] Further preferably, the polystyrene-polyisoprene-polystyrene triblock copolymer (SIS) is a linear copolymer, wherein the block ratio of polystyrene to polyisoprene is 16:84; and the viscosity average molecular weight of the polypropylene (PP) is 3000-5000.
[0014] Preferably according to the present invention, the cationic emulsifier is one or a combination of two or more of octadecyltrimethylammonium chloride, hexadecyltrimethylammonium chloride and hexadecyltrimethylammonium bromide, and hexadecyltrimethylammonium bromide is further preferred; compared with octadecyltrimethylammonium chloride and hexadecyltrimethylammonium bromide, hexadecyltrimethylammonium chloride exhibits better solubility and lower foaming rate at the same addition amount.
[0015] Preferably according to the present invention, the formate is sodium formate and / or potassium formate, more preferably potassium formate.
[0016] Preferably according to the present invention, the alcohol is ethanol, ethylene glycol or isopropanol, more preferably ethylene glycol; ethylene glycol can be mixed with water in any proportion, and after mixing, it can change the vapor pressure of water and significantly reduce the freezing point of water.
[0017] Preferably according to the present invention, the stabilizer is polyacrylamide, and the viscosity average molecular weight of the polyacrylamide is 10,000-30,000, more preferably 20,000.
[0018] According to the present invention, the method for preparing the antifreeze polymer / inorganic filler composite modified asphalt emulsion for drilling fluid comprises the following steps:
[0019] (1) adding a cationic emulsifier and a formate salt into water, stirring and dissolving the mixture to obtain a soap solution;
[0020] (2) heating the asphalt to 100-130° C., adding a composite filler, a polystyrene-polyisoprene-polystyrene triblock copolymer and polypropylene composite particles, and shearing to obtain a composite modified asphalt;
[0021] (3) Add the composite modified asphalt in step (2), the soap solution, alcohol substance and stabilizer in step (1) into a colloid mill, cool to 40° C., mix evenly, and obtain an antifreeze polymer / inorganic filler composite modified asphalt emulsion for drilling fluid.
[0022] Preferably according to the present invention, the stirring temperature in step (1) is 50-60°C.
[0023] Preferably, according to the present invention, in step (2), the asphalt is heated to 100-130°C and stirred for 10-20 minutes, and then the composite filler, polystyrene-polyisoprene-polystyrene triblock copolymer and polypropylene composite particles are added; the shearing is performed using a high-speed shearing machine, the shear rate is 1500-2500r / min, and the shearing time is 20-40min.
[0024] According to the present invention, the application of the antifreeze polymer / inorganic filler composite modified asphalt emulsion for drilling fluid in water-based drilling fluid is used to improve the inhibition, anti-collapse and plugging performance of the water-based drilling fluid.
[0025] The technical features and beneficial effects of the present invention are as follows:
[0026] 1. Small molecule alcohols and formates are introduced into the composite modified asphalt emulsion of the present invention. The synergistic effect of the two can reduce the freezing point of the asphalt emulsion from -5°C to about -25°C, significantly reducing the freezing point of the composite modified asphalt emulsion and improving its colloidal stability at low temperatures. At the same time, the introduction of small molecule alcohols and formates also plays an inhibitory synergistic effect, thereby improving the asphalt emulsion's ability to inhibit, plug and prevent collapse. The composite modified asphalt emulsion of the present invention has a wide freezing point range, which can be from -5°C to -25°C.
[0027] 2. The composite filler is introduced into the composite modified asphalt emulsion of the present invention, which can improve the sealing efficiency and temperature resistance of the cationic emulsified asphalt; the introduction of SIS / PP composite particles can increase the overall relative molecular mass, which can significantly improve the high temperature resistance and low temperature cracking resistance of the asphalt.
[0028] 3. The composite modified asphalt emulsion of the present invention has high temperature resistance and plugging performance, and also has excellent low-temperature storage stability. DETAILED DESCRIPTION
[0029] The present invention is further described below by means of specific examples, but is not limited thereto.
[0030] The raw materials used in the examples are all conventional raw materials and can be obtained commercially; the methods described are all prior art unless otherwise specified.
[0031] The polystyrene-polyisoprene-polystyrene triblock copolymer (SIS) used in the examples is available from Sinopec Baling Petrochemical Co., Ltd., model number YH-1126;
[0032] The viscosity average molecular weight of the polypropylene used in the examples is 4,000.
[0033] The asphalt used in the examples is petroleum asphalt with a softening point of 80°C.
[0034] Example 1
[0035] An antifreeze polymer / inorganic filler composite modified asphalt emulsion for drilling fluid is prepared from the following raw materials in parts by mass: 100 parts of asphalt, 32 parts of composite filler, 24 parts of polystyrene-polyisoprene-polystyrene triblock copolymer and polypropylene composite particles, 8 parts of cationic emulsifier, 14 parts of formates, 54 parts of alcohols, 6 parts of stabilizer, and 150 parts of water;
[0036] The composite filler is a mixture of spherical calcium carbonate, flaky mica flakes and sepiolite fibers, wherein the mass ratio of the spherical calcium carbonate, the flaky mica flakes and the sepiolite fibers is 1:2:1, and the particle size of the composite filler is 600 meshes; the cationic emulsifier is hexadecyltrimethylammonium bromide; the formate is potassium formate; the alcohol is ethylene glycol; and the stabilizer is polyacrylamide with a viscosity-average molecular weight of 20,000;
[0037] The polystyrene-polyisoprene-polystyrene triblock copolymer and polypropylene composite particles (SIS-PP particles) are prepared according to the following method: polystyrene-polyisoprene-polystyrene triblock copolymer (SIS) and polypropylene (PP) are added into a double-roller open mill, mixed evenly, hot-mixed to make the rubber material reach 100° C., mixed at 100° C. for 25 minutes to achieve mixed plasticization, then compression molded into sheet strips, and cut into 40-mesh particles using a pelletizer, namely polystyrene-polyisoprene-polystyrene triblock copolymer and polypropylene composite particles (SIS-PP particles); the mass ratio of the polystyrene-polyisoprene-polystyrene triblock copolymer (SIS) to polypropylene (PP) is 6:1.
[0038] The method for preparing the antifreeze polymer / inorganic filler composite modified asphalt emulsion for drilling fluid comprises the following steps:
[0039] (1) Preparation of soap solution: cationic emulsifier and formate are added to water and stirred magnetically at 55°C to dissolve the compounds and form a uniform soap solution.
[0040] (2) Asphalt was weighed and added into a metal stirring container. The mixture was continuously heated to 100°C using a heating device and mechanically stirred for 15 min. The composite filler and SIS-PP particles were added into the asphalt respectively. Subsequently, the asphalt was sheared at a high speed (speed of 2000 r / min) using a high-speed shearing machine for 30 min to obtain a composite modified asphalt.
[0041] (3) Preparation of composite modified asphalt emulsion: Add the composite modified asphalt in step (2), the soap solution, alcohols and stabilizer in step (1) into a colloid mill, cool to 40° C. by condensation, mix evenly, cool, and prepare an antifreeze-type polymer / inorganic filler composite modified asphalt emulsion for drilling fluid.
[0042] Example 2
[0043] An antifreeze polymer / inorganic filler composite modified asphalt emulsion for drilling fluid is as described in Example 1, except that the cationic emulsifier is 4 parts, and the other conditions are the same as in Example 1.
[0044] Example 3
[0045] An antifreeze polymer / inorganic filler composite modified asphalt emulsion for drilling fluid is as described in Example 1, except that the amount of formate is 5 parts, and the other conditions are the same as in Example 1.
[0046] Example 4
[0047] An antifreeze polymer / inorganic filler composite modified asphalt emulsion for drilling fluid is as described in Example 1, except that the composite filler is 20 parts, and the other conditions are the same as in Example 1.
[0048] Example 5
[0049] An antifreeze polymer / inorganic filler composite modified asphalt emulsion for drilling fluid is as described in Example 1, except that the polystyrene-polyisoprene-polystyrene triblock copolymer and polypropylene composite particles are 15 parts, and the other conditions are the same as in Example 1.
[0050] Example 6
[0051] An antifreeze polymer / inorganic filler composite modified asphalt emulsion for drilling fluid is as described in Example 1, except that the alcohol is 40 parts, and the other conditions are the same as in Example 1.
[0052] Example 7
[0053] An antifreeze polymer / inorganic filler composite modified asphalt emulsion for drilling fluid is as described in Example 1, except that the stabilizer is 3 parts, and the other conditions are the same as in Example 1.
[0054] Comparative Example 1
[0055] A modified asphalt emulsion for drilling fluid is as described in Example 1, except that no cationic emulsifier is added.
[0056] Comparative Example 2
[0057] A modified asphalt emulsion for drilling fluid is as described in Example 1, except that no composite filler is added.
[0058] Comparative Example 3
[0059] A modified asphalt emulsion for drilling fluid is as described in Example 1, except that no alcohol is added.
[0060] Comparative Example 4
[0061] A modified asphalt emulsion for drilling fluid is as described in Example 1, except that no formate is added.
[0062] Comparative Example 5
[0063] A modified asphalt emulsion for drilling fluid is as described in Example 1, except that polystyrene-polyisoprene-polystyrene triblock copolymer and polypropylene composite particles (SIS-PP particles) are not added.
[0064] Comparative Example 6
[0065] A modified asphalt emulsion for drilling fluid is as described in Example 1, except that ethylene glycol is replaced by propylene glycol.
[0066] Comparative Example 7
[0067] A modified asphalt emulsion for drilling fluid is as described in Example 1, except that potassium formate is replaced by potassium acetate.
[0068] Comparative Example 8
[0069] A modified asphalt emulsion for drilling fluid is as described in Example 1, except that the amount of potassium formate added is increased to 10 parts.
[0070] Comparative Example 9
[0071] A modified asphalt emulsion for drilling fluid is as described in Example 1, except that the mass ratio of SIS to PP in the polystyrene-polyisoprene-polystyrene triblock copolymer and polypropylene composite particles is 3.5:1.
[0072] Comparative Example 10
[0073] A modified asphalt emulsion for drilling fluid is as described in Example 1, except that the amount of SIS-PP composite particles added is increased to 40 parts.
[0074] Comparative Example 11
[0075] A modified asphalt emulsion for drilling fluid is as described in Example 1, except that no polyacrylamide stabilizer is added.
[0076] Test example
[0077] The antifreeze polymer / inorganic filler composite modified asphalt emulsion for drilling fluid prepared in the examples and comparative examples was evaluated as follows: basic physical properties, basic performance analysis before and after aging, and sand bed plugging performance.
[0078] 1. Basic physical properties
[0079] 1) Water dispersibility
[0080] Add 50 mL of distilled water to a 100 mL beaker, add 0.5 g of sample, stir on a magnetic stirrer for 30 min, and observe whether there is any floating matter.
[0081] 2) Colloidal stability
[0082] Take 100 mL of the stirred sample and place it in a 100 mL stoppered measuring cylinder. After standing at room temperature for 24 h, read the volume of the precipitated upper clear liquid or lower clear liquid and calculate the colloidal stability by formula (1).
[0083]
[0084] In formula (1), W is the colloidal stability, %; V is the volume of the clear liquid precipitated from the upper or lower part of the measuring cylinder after 24 hours, mL.
[0085] 3) Relative inhibition
[0086] Weigh 10.00 g of sodium bentonite for drilling fluid test that has been dried at 105±3°C for 4 hours and put it into a shale expansion cylinder. Apply a pressure of 2.85 MPa on the press and maintain it for 5 minutes. Remove and install it on a shale dilatometer to measure the expansion height of the core after soaking for 6 hours in 10% (10 g per 100 mL of water) KCl solution and 3% (3 g per 100 mL of water) sample solution.
[0087]
[0088] Where: Y is the relative inhibition; h1 represents the expansion height of the core after immersion in 3% sample solution, mm; h2 represents the expansion height of the core after immersion in 10% KCl solution, mm.
[0089] 4) Freezing point test
[0090] The freezing point of each example and comparative example sample was measured according to SY / T 0541-2009 standard.
[0091] 5) The test results of water dispersibility, colloid stability, relative inhibition and freezing point are shown in Table 1;
[0092] Table 1 Basic physical properties test results
[0093]
[0094]
[0095] As can be seen from Table 1, the performance parameters of Example 1 are excellent, and the sample solidification point reaches -27.5°C, which can meet the requirements of low-temperature on-site transportation and storage in drilling. Compared with Example 1, the reduction or non-addition of cationic emulsifier in Example 2 and Comparative Example 1 will affect the stability of the asphalt emulsion, so its colloidal stability and dispersibility in water will be weakened. In Example 3, Example 6, Comparative Example 3 and Comparative Example 4, formate and alcohol were reduced or not added, respectively, and the relative inhibition and freezing point of the asphalt emulsion were affected. This is because formates and alcohols can effectively lower the freezing point of water and enhance the low-temperature stability of the asphalt emulsion. In addition, formates and alcohols can effectively inhibit the hydration of clay minerals; in Comparative Example 6, ethylene glycol was changed to propylene glycol, and the low-temperature resistance of the asphalt emulsion was significantly reduced; in Comparative Example 7, potassium formate was changed to potassium acetate, and the relative inhibition and low-temperature frost resistance of the asphalt emulsion were reduced, indicating that the specific formates of the present invention can also effectively lower the freezing point of water, enhance the low-temperature stability of the asphalt emulsion, and effectively inhibit the hydration expansion of clay minerals; in Comparative Example 8, the amount of potassium formate added was increased, which weakened the colloidal stability of the asphalt emulsion, but did not produce significant changes in the relative inhibition and freezing point, and had a certain impact on the overall stability of the asphalt emulsion. In Example 7, the amount of stabilizer polyacrylamide was reduced, and the colloidal stability of the emulsion was reduced. This is because the reduction in the amount of polyacrylamide will affect the consistency of the emulsion system, thereby reducing the stability of the system; in Comparative Example 11, no stabilizer was added, which had a great impact on the colloidal stability of the asphalt emulsion, and the stability of the asphalt emulsion was reduced. In Comparative Example 10, the amount of SIS-PP composite particles was increased, and the colloidal stability and water dispersibility of the asphalt emulsion were both deteriorated. This is due to the high polarity of SIS-PP, which will affect the water dispersibility of asphalt. In addition, it can be seen from Examples 4, 5, Comparative Example 2, Comparative Example 5 and Comparative Example 9 that the composite filler and the polystyrene-polyisoprene-polystyrene triblock copolymer and polypropylene composite particles have little effect on the stability, inhibition and low-temperature antifreeze performance of the asphalt emulsion.
[0096] 2. Basic performance analysis before and after aging
[0097] In order to study the influence of aging on the basic properties of antifreeze polymer / inorganic filler composite modified asphalt emulsion before and after aging, the modified asphalt was first subjected to short-term aging by RTFOT in a rotary thin film oven at 90°C for 75 minutes. The basic properties of the polymer / inorganic filler composite modified asphalt emulsion before and after RTFOT short-term aging were tested, including needle penetration, softening point, and ductility tests, and the results are shown in Table 2.
[0098] Table 2 Basic performance analysis before and after aging
[0099]
[0100]
[0101] As can be seen from Table 2, compared with the original asphalt, the emulsification point of the composite modified asphalt in the embodiment and the comparative example increases, the penetration decreases, and the ductility increases to varying degrees, which shows that the overall plasticity and high temperature resistance of the composite modified asphalt are improved. Among them, the basic performance of Example 1 before and after aging is the most excellent. Compared with Example 1, the amount of composite filler added in Example 4 and Comparative Example 2 is reduced to varying degrees, the softening point decreases, the penetration increases, and the ductility decreases, indicating that the addition of composite filler significantly improves the temperature resistance of modified asphalt, and its addition amount is reduced, and the temperature resistance is poor. Compared with Example 1, the amount of SIS / PP particles added in Example 5 and Comparative Example 5 is reduced to varying degrees, and there is the same experimental trend as reducing the amount of composite filler. This is because the lipophilic groups in the SIS / PP particles adsorb the low molecular weight aromatics of the asphalt to form a new regional structure, and the overall relative molecular mass increases, so that the temperature resistance of the composite modified asphalt is improved. Compared with Example 1, Comparative Example 9 reduces the mass ratio of SIS to PP, and also has the same change rule, which is because the temperature resistance of SIS is better than PP.
[0102] 3. Sand bed plugging
[0103] Preparation of base slurry: Measure 400 mL of clean water and place it in a high-stirring cup, stir it at high speed (speed is 5000 r / min), then slowly add 16 g of drilling-grade bentonite and 0.56 g of Na2CO3 into the cup respectively, seal and stir at low speed for 24 hours at room temperature (speed is 800 r / min) to obtain 4% bentonite base slurry, prepare multiple portions of the above base slurry for later use.
[0104] This experiment uses a visual sand bed plugging device. First, measure 350cm 3 200 mesh quartz sand was loaded into a test glass cylinder and compacted and flattened; 2% (2 g per 100 mL of base slurry) of the example and comparative example samples were added to the 4% base slurry, and the added base slurry was loaded into the test glass cylinder of the sand bed plugging device. Under 0.7 MPa conditions, the penetration depth of the 15 min base slurry and the added base slurry into the sand bed was tested. The experimental results are shown in Table 3.
[0105] Table 3 Sand bed plugging test results
[0106]
[0107]
[0108] As shown in Table 3, compared with the original asphalt, the drilling fluids added with the composite modified asphalt of the embodiment and the comparative example both effectively blocked the sand bed, and the depth of Example 1 was only 12 mm. Compared with Example 1, the amount of composite filler added in Example 4 and Example 2 was reduced, and the sand bed blocking test results became worse, because the composite filler can form a "rigid and soft" composite block with asphalt to improve the blocking efficiency; in Example 5 and Comparative Example 5, the amount of SIS-PP particles was reduced, and the sand bed blocking test results also became worse, because SIS-PP particles can adsorb with asphalt to form a regional structure, improving the blocking performance of the sand bed; in Comparative Example 9, the mass ratio of SIS to PP was reduced, and the penetration depth of the sand bed was increased, which is due to the fact that SIS has many rigid groups, high strength, and certain blocking performance.
Claims
1. An antifreeze polymer / inorganic filler composite modified asphalt emulsion for drilling fluid, characterized in that: The method is prepared from the following raw materials in parts by weight: 80-120 parts of asphalt, 20-40 parts of composite filler, 15-30 parts of polystyrene-polyisoprene-polystyrene triblock copolymer and polypropylene composite particles, 4-12 parts of cationic emulsifier, 5-20 parts of formates, 40-60 parts of alcohols, 3-8 parts of stabilizers, and 150 parts of water; The asphalt is petroleum asphalt, and the softening point of the asphalt is 80-120°C; The composite filler is a mixture of spherical calcium carbonate, flaky mica flakes and sepiolite fibers, wherein the mass ratio of the spherical calcium carbonate, the flaky mica flakes and the sepiolite fibers is 1-1.5:1.5-3:1; The polystyrene-polyisoprene-polystyrene triblock copolymer and polypropylene composite particles are prepared according to the following method: polystyrene-polyisoprene-polystyrene triblock copolymer and polypropylene are added to a double-roll open mill, mixed evenly, hot-mixed to make the rubber material reach 100° C., mixed at 100° C. for 20-30 minutes to achieve mixed plasticization, then pressed into a sheet strip, and cut into 30-50 mesh particles using a pelletizer, to obtain the obtained particles; the mass ratio of the polystyrene-polyisoprene-polystyrene triblock copolymer to the polypropylene is 4.5-7:1; The cationic emulsifier is one or a combination of two or more of octadecyltrimethylammonium chloride, hexadecyltrimethylammonium chloride and hexadecyltrimethylammonium bromide; The alcohol is ethanol, ethylene glycol or isopropanol; the stabilizer is polyacrylamide.
2. The antifreeze polymer / inorganic filler composite modified asphalt emulsion for drilling fluid according to claim 1, characterized in that: The particle size of the composite filler is 400-800 meshes.
3. The antifreeze polymer / inorganic filler composite modified asphalt emulsion for drilling fluid according to claim 1, characterized in that: The polystyrene-polyisoprene-polystyrene triblock copolymer is a linear copolymer, wherein the block ratio of polystyrene to polyisoprene is 16:84; and the viscosity average molecular weight of the polypropylene is 3000-5000.
4. The antifreeze polymer / inorganic filler composite modified asphalt emulsion for drilling fluid according to claim 1, characterized in that: The cationic emulsifier is cetyltrimethylammonium bromide.
5. The antifreeze polymer / inorganic filler composite modified asphalt emulsion for drilling fluid according to claim 1, characterized in that: The formate is sodium formate and / or potassium formate.
6. The antifreeze polymer / inorganic filler composite modified asphalt emulsion for drilling fluid according to claim 1, characterized in that: The viscosity average molecular weight of the polyacrylamide is 10000-30000.
7. The method for preparing the antifreeze polymer / inorganic filler composite modified asphalt emulsion for drilling fluid according to claim 1 comprises the following steps: (1) Add cationic emulsifier and formate into water, stir and dissolve to obtain soap solution; (2) heating the asphalt to 100-130° C., adding composite filler, polystyrene-polyisoprene-polystyrene triblock copolymer and polypropylene composite particles, and shearing to obtain composite modified asphalt; (3) Add the composite modified asphalt in step (2), the soap solution, alcohol substance and stabilizer in step (1) into a colloid mill, cool to 40° C., and mix evenly to obtain an antifreeze polymer / inorganic filler composite modified asphalt emulsion for drilling fluid.
8. The method for preparing the antifreeze polymer / inorganic filler composite modified asphalt emulsion for drilling fluid according to claim 7, characterized in that: The stirring temperature in step (1) is 50-60°C; In step (2), the asphalt is heated to 100-130° C. and stirred for 10-20 minutes, and then the composite filler, polystyrene-polyisoprene-polystyrene triblock copolymer and polypropylene composite particles are added; the shearing is performed using a high-speed shearing machine, the shear rate is 1500-2500 r / min, and the shearing time is 20-40 minutes.
9. Use of the antifreeze polymer / inorganic filler composite modified asphalt emulsion for drilling fluid according to claim 1 in water-based drilling fluid to improve the inhibition, anti-collapse and plugging performance of water-based drilling fluid.
Citation Information
Patent Citations
SBS polymer modified emulsified asphalt and preparation method
CN102863804A
High-softening-point emulsified asphalt and preparing method and application thereof
CN105968834A
Low softening point emulsified asphalt for drilling fluid, and preparation method thereof
CN103265816A
Nano particle composite emulsion and preparation method
CN108239526A